2009
DOI: 10.1016/j.neuroscience.2009.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Increased phasic dopamine signaling in the mesolimbic pathway during social defeat in rats

Abstract: While reward-dependent facilitation of phasic dopamine signaling is well documented at both the cell bodies and terminals, little is known regarding fast dopamine transmission under aversive conditions. Exposure to aggressive confrontation is extremely aversive and stressful for many species including rats. The present study used fast-scan cyclic voltammetry and multiunit recording to determine if aggressive encounters and subsequent social defeat affect burst firing of ventral tegmental area (VTA) dopamine ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
170
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(184 citation statements)
references
References 71 publications
10
170
1
1
Order By: Relevance
“…It is thus possible that firing patterns composed of bursts followed by pauses mediate a different signal than isolated bursts associated with rewards. This is in accord with observations of increased burst firing with stressful stimuli (Moore et al, 2001;Anstrom and Woodward, 2005;Anstrom et al, 2009). In this context, our results indicate that the important signal in "spontaneous burst firing" may be the pauses between bursts.…”
Section: Transients Map Linearly Onto Receptor Occupancysupporting
confidence: 93%
“…It is thus possible that firing patterns composed of bursts followed by pauses mediate a different signal than isolated bursts associated with rewards. This is in accord with observations of increased burst firing with stressful stimuli (Moore et al, 2001;Anstrom and Woodward, 2005;Anstrom et al, 2009). In this context, our results indicate that the important signal in "spontaneous burst firing" may be the pauses between bursts.…”
Section: Transients Map Linearly Onto Receptor Occupancysupporting
confidence: 93%
“…Previous studies in resident-intruder tests have shown that DA and 5-HT Effect of encounter stimulation in isolated mice Y Ago et al systems are involved in aggressive and defeat behaviors during the encounter (Anstrom et al, 2009;Ferrari et al, 2003;Tidey and Miczek, 1996;van Erp and Miczek, 2000). It appears that the effects of the encounter in resident-intruder tests are related to both psychological and physical stress.…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that interactions between the resident mouse and an intruder mouse are necessary for these increases in prefrontal DA and 5-HT in male isolation-reared mice. Previous studies have shown that prefrontal DA levels are higher during or after an aggressive encounter in both attacking and defending rats (Anstrom et al, 2009;Tidey and Miczek, 1996;van Erp and Miczek, 2000). Furthermore, exposure to tests of 'anxiety', such as the social interaction test, causes an increase in hippocampal 5-HT release in rats from the more anxious Wistar strain, but not in rats from the less anxious SpragueDawley strain (Rex et al, 2004).…”
Section: Effect Of Encounter Stimulation In Isolated Mice Y Ago Et Almentioning
confidence: 93%
See 1 more Smart Citation
“…Discrete aversive stimuli evoke pauses in the firing rate of a clear majority of dopamine neurons (Cohen et al, 2012;Matsumoto and Hikosaka, 2009;Mirenowicz and Schultz, 1996) and suppress phasic dopamine release in the NAc (Badrinarayan et al, 2012;Oleson et al, 2012;Roitman et al, 2008;Wheeler et al, 2011; but also see Anstrom et al, 2009;Brischoux et al, 2009;Budygin et al, 2012;Park et al, 2015 for reported increases in phasic dopamine activity to aversive stimuli under some conditions). However, while discrete stimuli are commonly used to study phasic dopamine responses, the time domain of aversive stimuli can range from discrete to prolonged.…”
Section: Introductionmentioning
confidence: 99%